Securing a Place : Small-Scale Artisans in Modern Indonesia - Morrell, Elizabeth (Book collections on Project MUSE., 2018)
This book describes artisans from South Sulawesi, Indonesia, as they attempt to overcome poverty and communicate ethnic identity through participation in fluctuating silk and tourist souvenir industries. Morrell assesses the significance and long-term sustainability of their activities. The discussion addresses broad questions about economic development, as microenterprises such as these are vital sources of non-farm incomes in rural areas with high unemployment.